2018
DOI: 10.1111/jgs.15497
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Brain Amyloid Deposition and Instrumental Activities of Daily Living in Older Adults: A Longitudinal Study from the Multidomain Alzheimer Prevention Trial

Abstract: Amyloid-positive and -negative older adults are likely to have different trajectories in IADL performance. Future research is needed to better understand the relationship between amyloid plaques and functional limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…Prior studies in CN participants have shown associations between amyloid burden and objective and subjective cognitive function 23–26 but only limited evidence for a relationship with IADL difficulties 16,17 . The current analyses demonstrated an association among IADL, amyloid burden, objective cognition, and subjective cognitive concerns.…”
Section: Discussioncontrasting
confidence: 48%
“…Prior studies in CN participants have shown associations between amyloid burden and objective and subjective cognitive function 23–26 but only limited evidence for a relationship with IADL difficulties 16,17 . The current analyses demonstrated an association among IADL, amyloid burden, objective cognition, and subjective cognitive concerns.…”
Section: Discussioncontrasting
confidence: 48%
“…Current findings are in line with a recent study suggesting that amyloid‐positive and ‐negative individuals might have different IADL trajectories, 1 with previous studies suggesting that baseline MRI biomarkers could predict IADL worsening over time regardless of cognitive status 10 and that higher disability in ADL ability is associated with greater pathological burden (e.g., neuritic plaque and neurofibrillary tangle counts) in patients with dementia due to AD 30 . A review 31 showed that neuroanatomical changes (e.g., hippocampal atrophy, white matter changes) were associated with IADL, independent of cognition, but to a lesser extent; cognitive function seemed to be a stronger IADL predictor than brain morphological changes.…”
Section: Discussionsupporting
confidence: 92%
“…IADL are complex, involving multiple higher cognitive functions, are important for autonomous living and decline earlier than more basic ADL. Although cognitive outcomes in association with brain amyloid accumulation have been described more thoroughly, functional trajectories of activities of daily living have been studied in less detail 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here a secondary analysis of the Multidomain Alzheimer's Preventive Trial (MAPT), whose methods have been published elsewhere 21‐26 (see Supplementary Appendix S1). This randomized controlled trial assessed the cognitive impact of a 3‐year multidomain intervention, supplementation with omega‐3 fatty acids, or their combination, in 1,679 participants.…”
Section: Methodsmentioning
confidence: 99%